Metabolic power and energy expenditure in the German Bundesliga - Venzke, Jan; Weber, Hendrik; Schlipsing, Marc; Salmen, Jan; Platen, Petra (Frontiers in Physiology, 2023)
The aims of the study were to analyze metabolic power (MP) and MP derived parameters for different positions in the German Soccer Bundesliga and to evaluate if classification of high-intensity is more suited using the metabolic power approach instead of using traditional speed-based methods. 1345 video match analysis (25 Hz) datasets from 419 players in 96 matches of the German 1st Bundesliga were gathered by an automatic player tracking system. Displacement (speed, acceleration, distance) and energetic (MP, energy expenditure) variables were determined. Intensity was classified utilizing conventional thresholds. Metabolic and running profiles were compared among six positional groups and between the halves of the match respectively (one-way ANOVA). Further, time spent, distance covered and energy expended at high speed (>15.5 km·h-1) and high acceleration (> 2 m s-2) were compared to those at high MP (>20 W·kg-1) (one-way ANOVA) for evaluating if metabolic power is more suited to describe intensity in team sports Main findings are that central-attacking midfielders (CAM) and central midfielders (CM) expended more energy (CAM: 59.8±4.2 kJ·kg-1; CM: 59.6±3.6 kJ·kg-1) and covered more distance (CAM: 11494±765 m; CM: 11445±638 m) than all other positions (p<0.001). In the whole group of players, less time (t) and less energy (EE) were extended in high speed (t: 302±84 s; EE: 10.1±2.9 kJ·kg-1) and at high acceleration zones (t: 147±24 s; EE: 5.5±1.2 kJ·kg-1) when compared to high MP zone (t: 617±141 s; EE: 20.0±4.4 kJ·kg-1) (p<0.001). Furthermore, players covered more distance at high MP (2464±597 m) than at high speed (1638±458 m) and much less at high acceleration (359±67 m) (p<0.001). The higher activity profiles of CAM and CM compared to the other positions indicate the need for higher developed physiological performance in players of these positions. High intensity activities should be interpreted differently when using MP and displacement parameters as indicators of high intensity in soccer.